2020
DOI: 10.1016/j.jaccas.2019.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Left-Sided Humerus Fracture as an Unusual Complication of Defibrillation Threshold Testing Following S-ICD Implantation

Abstract: Comminuted subcapital humerus fracture as a complication of subcutaneous implantable cardioverter-defibrillator insertion is related to an abducted and externally rotated arm position during the defibrillation threshold test at which the current pathway is through the pectoral muscle. It is advisable to adduct the arm before defibrillation threshold testing. ( Level of Difficulty: Beginner. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…With the introduction of every new technology, we must learn how to omitclar and deal with new types of complications. That was exactly what happened to Elder and Al Hashimi ( 1 ), who were kind enough to share their experience in this issue of JACC: Case Reports , which we have read with a great interest. Their case presents an uncommon mechanical complication of defibrillation threshold testing (DFT) following subcutaneous implantable cardioverter-defibrillator (S-ICD) implantation, resulting in a left subcapital humerus bone fracture.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…With the introduction of every new technology, we must learn how to omitclar and deal with new types of complications. That was exactly what happened to Elder and Al Hashimi ( 1 ), who were kind enough to share their experience in this issue of JACC: Case Reports , which we have read with a great interest. Their case presents an uncommon mechanical complication of defibrillation threshold testing (DFT) following subcutaneous implantable cardioverter-defibrillator (S-ICD) implantation, resulting in a left subcapital humerus bone fracture.…”
mentioning
confidence: 56%
“…S-ICDs are being implanted worldwide with growing evidence regarding their efficacy and safety; therefore, Elder and Al Hashimi ( 1 ) have proposed that an adducted position of the arm before DFT in S-ICD recipients to prevent the described complication is especially important to improve the overall safety of S-ICD implantation.…”
mentioning
confidence: 99%
“…Nineteen S-ICD implantation procedures (95%) in the US-SAPB group went without any complications. One patient experiences a comminuted left-sided subcapital humerus fracture probably as a result of the positioning of the arm (abducted and externally rotated) during the defibrillation test at which the current pathway is through the pectoral muscle causing a forceful contraction [16] .…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the patient with the subcapital humerus fracture as a result of the positioning of the arm (abducted and externally rotated) during the defibrillation threshold test we reviewed the case and concluded that it is advisable to adduct the arm before defibrillation testing in S-ICD implantation [16] .…”
Section: Discussionmentioning
confidence: 99%
“…The maximum energy output of the device is 80 J, and the value of 65 J is typically programmed for DFT to maintain a 15 J safety margin, although some reports prove that with correct implantation even lower values (20-40-50 J) can be efficient [ 87 , 88 , 89 ]. If patient’s arm was abducted for implantation, it should adducted back for DFT to avoid trauma during forceful muscle contraction occurring at VF induction [ 90 , 91 ]. A successful 65 J shock with correct impedance (40–140 Ohm) ends the test.…”
Section: Defibrillation Testingmentioning
confidence: 99%